Nicotine dependence is associated with an increased risk of developing chronic, non-communicable inflammatory disease: a large-scale retrospective cohort study - Kridin, Khalaf; Papara, Cristian; Bieber, Katja; De Luca, David A.; Klein, Jan Philipp; Ludwig, Marlene A.; Curman, Philip; Vorobyev, Artem; Dempfle, Astrid; Ludwig, Ralf J. (Frontiers in Psychiatry, 2025)
IntroductionChronic, non-communicable inflammatory diseases (CIDs) affect a large portion of the population, imposing a significant morbidity, encompassing a substantial mortality. Thus, they are a major medical burden with a high unmet need. CIDs develop over the span of several years, and the risk of developing CIDs has been linked to genetic and environmental factors. Thus, modification of environmental factors is a promising approach for the prevention of CIDs. Among modifiable environmental factors that have been linked to the CID risk is nicotine dependence. However, for only few CIDs, compelling evidence suggests that nicotine dependence increases (e.g., rheumatoid arthritis and asthma) or decreases (e.g., pemphigus) the CID risk. For most CIDs, there are inconsistent, scant, or no reports on the risk of CID associated with nicotine dependence.MethodsTo address this gap, we leveraged TriNetX, analyzing data from over 120 million electronic health records (EHRs). Using propensity score matching (PSM) to control for age, sex, ethnicity, and other CID risk factors, we contrasted the risk of developing any or any of the 38 CIDs in 881,192 EHRs from individuals with nicotine dependence to PSM-matched unexposed counterparts.ResultsThe analytical pipeline was validated by demonstrating an increased risk of individuals exposed to nicotine dependence for subsequent diagnosis of myocardial infarction, malignant neoplasm of the lung, and chronic obstructive pulmonary disease. Overall, 16.8% of individuals with nicotine dependence developed CIDs, compared to 9.6% of individuals not exposed to nicotine dependence (hazard ratio 2.12, confidence interval 2.10–2.14, p < 0.0001). Investigating single CIDs, nicotine dependence imposed increased risks for 23 of the 38 investigated diseases, i.e., dermatomyositis, granulomatosis with polyangiitis, pyoderma gangrenosum, and immune thrombocytopenic purpura. The sex-stratified analysis revealed few sex-specific differences in CID risk.DiscussionOur study emphasizes the importance of preventive measures targeting nicotine addiction to reduce the global burden of CIDs.